2004
DOI: 10.1080/07315724.2004.10719424
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Effect of the Magnesium Content of a Mineral Water in the Human Body

Abstract: Magnesia's high Mg (204 mg/M) and low Na (5.4 mg/L) content makes it an excellent source of Mg for patients suffering from heart problems and/or high blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 2 publications
1
15
0
1
Order By: Relevance
“…In general, Mg was bioavailable from all test products. This finding is consistent with the results of prior studies that revealed Mg bioavailability from mineral water and dietary supplements [1720,26]. Urinary Mg excretion increased after the consumption of all test products, and 24 h urinary Mg excretion did not significantly differ among the test products.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, Mg was bioavailable from all test products. This finding is consistent with the results of prior studies that revealed Mg bioavailability from mineral water and dietary supplements [1720,26]. Urinary Mg excretion increased after the consumption of all test products, and 24 h urinary Mg excretion did not significantly differ among the test products.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, subjects with low initial serum Mg levels, suggesting a severe tissue Mg deficiency, have remarkably elevated urinary Mg retention [20]. In this study, the fasting Mg levels of all participants were within the normal range.…”
Section: Discussionmentioning
confidence: 58%
“…The ion quotient ratio can be calculated for all living organisms. It affords better dietary and healthy characteristics than the simple Ca/Mg or Na/K ratios with concentrations given in moles (Kiss et al, 2004):…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Therefore, "junk food" is usually lacking this essential element. Tap water and/or mineral water can be a source of magnesium, but the amount varies according to the water source [4].…”
Section: Magnesium Deficiencymentioning
confidence: 99%